Sosialisasi Anti-Bullying Sebagai Upaya Pencegahan Perundungan di Lingkungan Sekolah Desa Berumbung Baru - Nizmi, Yusnarida Eka; Natahsya, Cindy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
This article describes how bullying is existed at SMPN 4 Dayun. Bullying shows up in various places, including in school environment. Bullying does not only shows up in big cities, but also in rural areas. Berumbung Baru is one of the villages in Dayun District, Siak Regency, which is the location of Kuliah Kerja Nyata Merdeka Belajar Kampus Merdeka (MBKM) of Social and Political Science Students focus on Membangun Kampung Program. The data was collected by doing interviews with the community, distributing questionnaires during the socialization program and reviewing articles from related literatures such as journals, documents, print and online media and other trusted sources. By doing Interview from the community, bullying has become something quite massive in Berumbung Baru area. It should be noticed that Berumbung Baru is one of the villages need information and socialization related to bullying intensively. Doing some significant efforts to prevent bullying by sharing information and socialization, especially to students in grade 3 of SMPN 4 Dayun and parents in Berumbung Baru are potential method. This article shows that the understanding of students, teachers, parents, and the Berumbung Baru community regarding bullying still needs to be optimized. If socialization and sharing information is not carried out intensively, bullying is uneasy to be stop.